The agrarian territory along the rivers in the Amazonas - Schwade, Tiago Maiká (2019)
In this work, we seek to contribute to the understanding of the agrarian territorial organization of the marginal lands and river islands in the state of Amazonas (Brazil). Therefore, we seek to answer the following questions: how was the process of territorial disputes on the banks of the Amazonian rivers? How is the marginal land and the river islands in the Amazon legally constituted? What are the mechanisms used in land ownership? How does the physical environment influence the appropriation of territory? We seek to analyze the territory from a materialistic perspective of science, and we start from the understanding that the territory is the result of social relations of production. The work is one of the results of the bibliographical and documentary survey carried out for the doctoral thesis "The formation of capitalist property in Amazonas" presented to the Graduate Program in Human Geography of USP in 2019. It also has a close relationship with the experience Amazon region of the author. This work highlights important aspects of the appropriation of the territory both from the historical and legal point of view, as well as the strategies of peasant reproduction in a constantly changing physical environment.